2010
DOI: 10.1186/cc8205
|View full text |Cite
|
Sign up to set email alerts
|

Clinical review: Fresh frozen plasma in massive bleedings - more questions than answers

Abstract: Fresh frozen plasma (FFP) is indicated for the management of massive bleedings. Recent audits suggest physician knowledge of FFP is inadequate and half of the FFP transfused in critical care is inappropriate. Trauma is among the largest consumers of FFP. Current trauma resuscitation guidelines recommend FFP to correct coagulopathy only after diagnosed by laboratory tests, often when overt dilutional coagulopathy already exists. The evidence supporting these guidelines is limited and bleeding remains a major ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 58 publications
0
72
1
1
Order By: Relevance
“…Durante the acute resuscitation of a trauma patient, fibrinogen is most commonly replaced by plasma transfusion. The content of a standard dose of CRYO is equivalent to the amount of fibrinogen found in an average adult dose of FFP (4 units), where each unit of FFP contains 0.5 g of fibrinogen Nascimento et al, 2010). There is little published literature in trauma patients to guide when CRYO is required and what the effective dose may be.…”
Section: Introductionmentioning
confidence: 99%
“…Durante the acute resuscitation of a trauma patient, fibrinogen is most commonly replaced by plasma transfusion. The content of a standard dose of CRYO is equivalent to the amount of fibrinogen found in an average adult dose of FFP (4 units), where each unit of FFP contains 0.5 g of fibrinogen Nascimento et al, 2010). There is little published literature in trauma patients to guide when CRYO is required and what the effective dose may be.…”
Section: Introductionmentioning
confidence: 99%
“…Not all investigators agreed and several suggested that increased amounts of plasma and platelets would cause an increase in the incidences of ARDS, TRALI, transfusion-associated circulatory overload, and other bloodrelated complications. 33,34 In an effort to programmatically determine optimal resuscitation practice balancing risk versus benefit, we embarked on a decade-long research effort. The Trauma Outcomes Group collected data from 466 massive transfusion patients from 16 level 1 centers from 2005 to 2006.…”
mentioning
confidence: 99%
“…Fresh frozen plasma is obtained via apheresis of whole blood and frozen within 8 h [59]. It contains all the clotting factors, fibrinogen, proteins C and S, and albumin.…”
Section: Blood Productsmentioning
confidence: 99%